2013
DOI: 10.11645/7.2.1793
|View full text |Cite
|
Sign up to set email alerts
|

Faculty and student perceptions and behaviours related to information literacy:

Abstract: This pilot study was developed to determine if the University’s students were proficient in information literacy (IL) based on the requisite skills defined by ALA (2000), to define faculty and student perceptions and behaviours related to IL and to test an evaluation rubric using empirical inquiry and triangulated methods. Findings suggested that not all students (n=164) had satisfactory IL skills even at the senior student level. While 4th year college students (seniors n=91) fared better on an IL survey when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…The reticence to use a variety of information sources could be related to lack of awareness of the sources, or a difficulty in locating and using them, and is worthy of further investigation. Ganley et al (2013) found an over-reliance on newspaper and popular websites with too few peer-reviewed articles and other scholarly material being used by students. This is supported by Morrison (2007) who 'expressed a desire for students to read published academic work ' (2007, p.12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reticence to use a variety of information sources could be related to lack of awareness of the sources, or a difficulty in locating and using them, and is worthy of further investigation. Ganley et al (2013) found an over-reliance on newspaper and popular websites with too few peer-reviewed articles and other scholarly material being used by students. This is supported by Morrison (2007) who 'expressed a desire for students to read published academic work ' (2007, p.12).…”
Section: Discussionmentioning
confidence: 99%
“…When researching academics' views two broad approaches have been adopted, using either a quantitative method drawing from sample groups taken across a number of institutions (Cope & Sanabria, 2014) or using a cross-section of disciplines, (DaCosta, 2010;Dubicki, 2013). Some researchers included a range of disciplines (Andretta et al, 2008;Bury, 2011) at one institution (McGuinness, 2006;Morrison, 2007;Saunders, 2012;Ganley, Gilbert & Rosario, 2013), or concentrated on a specific faculty's view (Leckie & Fullerton, 1999;Boon, Johnston & Webber, 2007). Academics were presented with lists of IL competencies skills which they selected and prioritised as important for students to possess.…”
Section: Subsequently Cilip Have Issued a New Definition Which Statesmentioning
confidence: 99%
“…Many studies examine perceptions of IL as a concept, particularly perceptions of instructional faculty and how they value IL as a literacy for their students (Bury, 2011;Bury, 2016;DaCosta, 2010;Dubicki, 2013;Kim & Shumaker, 2015;McAdoo, 2008;Pinto, 2016;Sandercock, 2016;Saunders, 2012). Additional studies have also examined faculty perceptions of student IL competency as well as student self-perceptions of IL skill (Freeman, 2004;Ganley et al, 2013;Jackson, MacMillan, & Sinotte, 2014;Kousar & Mahmood, 2015;Singh, 2005). These are valuable studies for the academic librarian profession: Using a similar approach can inform an understanding of faculty and student IL perceptions within the new theoretical context of the Framework.…”
Section: Doyle Foster and Yukhymenko-lescroart Development Of The Permentioning
confidence: 99%
“…[ RESEARCH ARTICLE ] Doyle, Foster, & Yukhymenko-Lescroart Development of the Perception of Information Literacy Scale from IL instruction (Freeman, 2004;Molteni & Chan, 2015), may believe they don't have anything new to learn about how to use and create information (M. Gross & Latham, 2009), and may generally struggle to demonstrate expected IL competencies at their academic level (Ganley, Gilbert, & Rosario, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Project Information Literacy (http://www.projectinfolit.org/) has published numerous reports about how college students search, find, and use information in schooling and everyday life settings. Gross and Latham (2009), Ganley (2013), Yearwood, Foasberg, and Rosenberg (2015), and Perry (2017) are further exemplars of investigations into perceptions of information literacy and related behaviors. This study continues in the mode of investigating instructor perceptions, but focuses on investigation and documentation of predictable misunderstandings in information literacy learning.…”
Section: Hinchliffe Rand and Collier Predictable Information Literacymentioning
confidence: 99%